The Investigation of Serum Homocysteine and Malondialdehyde Levels in Hypercholesterolemic Subjects - Gürsu, M. Ferit; Çıkım, Gürkan (Fırat University, 2001)
In this study we aimed at examining the relationship between malondialdehyde(MDA), one of the end product of lipid peroxidation and homocysteine one of the independent risk factor for coronary heart disease. Total of 48 hypercholesterolemic subjects were investigated. These subjects were divided into two groups according to their homocysteine levels. Patients in Group I (n=15) had high homocysteine levels (>15 µmol/1) whereas patients in Group II (n=33) had normal homocysteine levels (5-15 µmol/1). Group III was composed of 24 normocholesterdemic volunteers . The serum MDA levels of all subjects were measured . We found a statistically significant difference (p0.05) . When MDA levels of patients with high homocysteine (Group I) were compared with ones with normal homocysteine levels, we also found that there is a significant difference (p

Bu çalışmada oksidan stresin arttığı durumlarda düzeyi yükselen lipid peroksidasyonlarının son ürünlerinden olan malondialdehit (MDA) ile koroner kalp hastalığının (KKH) gelişiminde diğer risk bileşenlerinden bağımsız bir risk faktörü olan homosistein arasındaki ilişkiyi araştırmak amaçlanmıştır. Serum kolesterol düzeyi yüksek olan 48 hastada ve kontrol olarak alınan 24 normokolesterolemik kişide araştırma yapılmıştır. Çalışma, grup I hiperkolesterolemik ve homosistein düzeyleri yüksek (15 µmol/l >) olan 15 , grup II hiperkolesterolemik ve homosistein düzeyleri normal (5 - 15 µmol/1) olan 33 ile normokolesterolemik kontrol grubu grup III olarak 3 gruba ayrılmıştır. Grup I ile kontrol grubu olan grup III'ün serum MDA düzeyleri karşılaştırıldığı zaman istatistiksel olarak anlamlı bir farklılık bulunmuştur (p0.05) grup I ile grup II arasında yine istatistiksel olarak anlamlı bir farklılığın olduğu görülmüştür (p
HİPERKOLESTEROLEMİK KİŞİLERDE SERUM HOMOSİSTEİN İLE MALONDİALDEHİT DÜZEYLERİNİN ARAŞTIRILMASI